Debinding Mechanisms in Thermoplastic processing of a Ba0.5Sr0.5Co0.8Fe0.2O3−δ‐ Stearic Acid–Polystyrene Mixture. Issue 2 (23rd December 2012) - Salehi, Mehdi; Clemens, Frank; Otal, Eugenio H.; Ferri, Davide; Graule, Thomas; Grobéty, Bernard
Abstract In the present study, we address the interaction between a thermoplastic binder system and Ba0.5Sr0.5Co0.8Fe0.2O3−δ (BSCF) during thermal treatment of the thermoplastic feedstock. BSCF powder was coated with different amounts of stearic acid (SA) acting as a surfactant. Oxygen release from the uncoated BSCF surface changes the decomposition of polystyrene (PS) in inert atmospheres from a pyrolytic to a thermoxidative mechanism, thereby decreasing the break‐down temperature and the activation energy. In mixtures with coated BSCF powder, the decomposition products of SA carbonatize the BSCF surface, which inhibits oxygen release. Mass spectrometry of the breakdown products indicates that the decomposition of SA in the presence of BSCF also modifies the decomposition pathway of PS. The influence of BSCF on the polymer decomposition reaction in air is not as strong. Oxygen diffusion seems to be responsible for the differences to pure PS in reaction rates and the activation energies.